Quality of life following resective surgery: Initial outcomes - Tharakan, John (Universiti Sains Malaysia, 2009)
To determine the effect of surgery on the quality of life of patients diagnosed with drug-resistant epilepsy. Twelve patients, 9 males and 3 females (29.92±320 years) with refractory epilepsy who underwent amygdalohippocampectomy during the-period 2003-2007 and completed a minimum 1 year follow-up were included in the study. Illness duration was 16.83±3.41 years. Four of the patients had surgery on the left side, and the rest, on the right hemisphere. Quality of life was assessed using the Quality of Life in Epilepsy Inventory-31 (QOLIE-31 ), a Likert type scale, administered pre- and 1 year post-surgery. A 1-way ANOVA with repeated measures was used to determine the differences in selected subscales for normally distributed data. The Wilcoxon Signed Rank Test was employed for ordinal data. Significance level was set to 0.05. There were significant differences in seizure score after surgery (pre-surgery: 8.17±. 72, post-surgery: 1.92±.69, p=0.002, r=0.892). However, there were no significant changes over time in subscales assessing seizure worry (pre-surgery: 44.08±2.90, post surgery: 47.75±3.36, p=0.453, eta~.052), cognitive functioning (pre-surgery: 48.50±2.74, post-surgery: 48.75±329, p=0.932, eta~.001) and Social functioning (pre-surgery: 47.75±2.34, post-surgery: 49.42±2.85, p=0.606, eta~.025). In spite of significant differences in seizure score, the quality of life markers did not change accordingly. 'the small sample size may have been prohibitive in terms of reaching statistically significant differences over time. Other possible explanations offered for the discrepancy between the results of this study and what was reported in the literature include shorter post-assessment period and alternative quality of life assessment tool.